Children’s Character Education in Axiological Perspective: Tri Center Education Ki Hajar Dewantara - Zulfiani, Mei; Hidayat, Fahri (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Education is the path to change. The changes in question are not only changes in knowledge, but also changes in various things such as behavior, attitudes, and thinking patterns. Character education is one of the things that is currently very emphasized due to the declining morale of the prospective successors of this nation. Ki Hadjar Dewantara as one of the educational figures who has a lot of thoughts also has his own views related to children's character education. This study aims to analyze how the relevance of ki Hajar Dewantara thought with the current conditions. The results of this study is the role of the environment is very influential in the development of children's character, where the environment can form the character of children such as leadership, mutual help, and have responsibility.